Different Sources of Dietary Magnesium Supplementation Reduces Oxidative Stress by Regulation Nrf2 and NF-?B Signaling Pathways in High-Fat Diet Rats - Orhan, Cemal; Er, Besir; Deeh, Patrick Brice Defo; Bilgic, Ahmet Alp; Ojalvo, Sara Perez; Komorowski, James Richard; Şahin, Kazım (Springernature, 2021)
Magnesium (Mg) is an essential mineral required for many physiological processes, including ionic balances in ocular tissues. We compared the effects of different Mg-chelates (Mg oxide, MgO vs. Mg picolinate, MgPic) on retinal function in a high-fat diet (HFD) rats. Forty-two rats were divided into six groups and treated orally for 8 weeks as follows: Control, MgO, MgPic, HFD, HFD + MgO, and HFD + MgPic. Mg was administered at 500 mg of elemental Mg/kg of diet. HFD intake increased the levels of retinal MDA and NF-kappa B, INOS, ICAM, and VEGF but downregulated Nrf2. However, in rats supplemented with MgO and MgPic, the retinal MDA level was decreased, compared with the control and HFD rats. Activities of antioxidant enzymes (SOD, CAT, and GPx) were increased in HFD animals given Mg-chelates (p < 0.001), MgPic being the most effective. Mg supplementation significantly decreased the expression levels of NF-kappa B, INOS, ICAM, and VEGF in HFD rats while increasing the level of Nrf2 (p < 0.001). Mg supplementation significantly decreased the levels of NF-kappa B, INOS, ICAM, and VEGF and increased Nrf2 level in HFD rats (p < 0.001), with stronger effects seen from MgPic. Mg attenuated retinal oxidative stress and neuronal inflammation and could be considered as an effective treatment for ocular diseases.
Keywords: Magnesium oxide; Magnesium picolinate; Retina; Oxidative stress; Inflammation; High-fat diet